The hero with a thousand faces - Campbell, Joseph (Novato New World Library, 2008)
Since its release in 1949, The Hero with a Thousand Faces has influenced millions of readers by combining the insights of modern psychology with Joseph Campbell?s revolutionary understanding of comparative mythology. In these pages, Campbell outlines the Hero?s Journey, a universal motif of adventure and transformation that runs through virtually all of the world?s mythic traditions. He also explores the Cosmogonic Cycle, the mythic pattern of world creation and destruction.
Includes bibliographical references (p. 363-382) and index.
Keywords: Mythology